The feasibility of field collected pig oronasal secretions as specimens for the virologic surveillance of Japanese encephalitis virus - Chiou, Shyan-Song; Chen, Jo-Mei; Chen, Yi-Ying; Chia, Min-Yuan; Fan, Yi-Chin (PLOS Neglected Tropical Diseases, 2021)
Virologic surveillance of Japanese encephalitis virus (JEV) relies on collecting pig blood specimens and adult mosquitoes in the past. Viral RNAs extracted from pig blood specimens suffer from low detecting positivity by reverse transcription PCR (RT-PCR). The oronasal transmission of the virus has been demonstrated in experimentally infected pigs. This observation suggested oronasal specimens could be useful source in the virus surveillance. However, the role of this unusual route of transmission remains unproven in the operational pig farm. In this study, we explore the feasibility of using pig oronasal secretions collected by chewing ropes to improve the positivity of detection in commercial pig farms. The multiplex genotype-specific RT-PCR was used in this study to determine and compare the positivity of detecting JEV viral RNAs in pig’s oronasal secretions and blood specimens, and the primary mosquito vector. Oronasal specimens had the overall positive rate of 6.0% (95% CI 1.3%–16.6%) (3/50) to 10.0% (95% CI 2.1%–26.5%) (3/30) for JEV during transmission period despite the negative results of all blood-derived specimens (n = 2442). Interestingly, pig oronasal secretions and female Culex tritaeniorhynchus mosquito samples collected from the same pig farm showed similar viral RNA positive rates, 10.0% (95% CI 2.1%–26.5%) (3/30) and 8.9% (95% CI 2.5%–21.2%) (4/45), respectively (p> 0.05). Pig oronasal secretion-based surveillance revealed the seasonality of viral activity and identified closely related genotype I virus derived from the mosquito isolates. This finding indicates oronasal secretion-based RT-PCR assay can be a non-invasive, alternative method of implementing JEV surveillance in the epidemic area prior to the circulation of virus-positive mosquitoes.